2012
DOI: 10.14210/bjast.v16n2.p65-76
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura populacional e biologia reprodutiva do camarão-da-amazônia <i>Macrobrachium amazonicum</i> (Heller,1862) (Decapoda: Palaemonidae) em um estuário da região nordeste do Pará, Brasil

Abstract: This study aimed to investigate the abundance, population structure and reproductive characteristics (size at first maturity and spawning time) of the Amazon river prawn, Macrobrachium amazonicum, captured in northeast Pará, Brazil. This fishing resource is economically important in the area. M. amazonicum was abundant in the region during the study period (August/08 to July/09), especially in the Curral Velho community. During the rainy season however, there was an accentuated decrease in abundance of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
2
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 10 publications
6
25
2
14
Order By: Relevance
“…Studies conducted with the same species also demonstrated the occurrence of ovigerous females during all sampling months, but with peaks in some of them. Freire et al (2012) found a greater abundance of females with eggs in January and February. They reported that the peaks refer to better physiological conditions, i.e., higher accumulation of energy during reproductive periods; while Silva (2011) observed a higher frequency of ovigerous females from September to November and in January, pointing out that this occurred in raining periods.…”
Section: Discussionmentioning
confidence: 89%
“…Studies conducted with the same species also demonstrated the occurrence of ovigerous females during all sampling months, but with peaks in some of them. Freire et al (2012) found a greater abundance of females with eggs in January and February. They reported that the peaks refer to better physiological conditions, i.e., higher accumulation of energy during reproductive periods; while Silva (2011) observed a higher frequency of ovigerous females from September to November and in January, pointing out that this occurred in raining periods.…”
Section: Discussionmentioning
confidence: 89%
“…M. amazonicum represents the main freshwater shrimp, presenting a fast development and wide adaptive plasticity to the several environments (Vergamini et al, 2011). In terms of the seasonal changes observed in the diet of the carcinophagous guild, these may be the result of the water level increase in the reservoir providing new shelters for the shrimps, hampering their capture (Freire et al, 2012), besides the carried sediment influencing the water transparency, slowing the phytoplankton growth, making food more restricted to the individuals, factors which may also decrease the shrimp availability. However, the reduction of the water volume promotes the decrease in the colonization area, sediment precipitation occurs, increasing the water transparency and the insolation allowing the proliferation of microalgae, food for the shrimp, and consequently, a greater availability of these individuals may occur.…”
Section: Discussionmentioning
confidence: 99%
“…This great environmental plasticity of the species has been related to intraspecific differences ranging from morphological characteristics (Porto, 2004) to genetic variations (Peixoto, 2002;Pileggi and Mantelatto, 2010;Vergamini et al, 2011) which might reflect specific conditions of survival, development, reproduction, focused on artificial environments (Coelho et al, 1982;Lobão et al, 1996;Moraes-Riodades and Valenti, 2002;Moraes-Valenti and Valenti, 2007;Marques et al, 2012). Relative growth in natural populations are poorly known (Flexa et al, 2005;Silva et al, 2007;Bentes et al, 2011;Freire et al, 2012) and the available data are not yet sufficient for a satisfactory comprehension of the plasticity of the species in relation to environmental changes in the many Amazon ecosystems (Maciel and Valenti, 2009).…”
Section: Thementioning
confidence: 99%